Rekonstruksi Materi Pembinaan Pendidikan Islam Masa Nabi di Tengah Dekadensi Moral Pada Era Disrupsi - Fitriani, Fitriani; Kurahman, Opik Taupik; Suhartini, Andewi (UIR Press, 2023)
The purpose of this research is to reconstruct the material for fostering Islamic education during the Prophet's era for students in the midst of moral decadence in the era of disruption. This research uses a qualitative type method, with a library research approach, using content analysis data analysis techniques. Islamic education materials in the current era must be adaptive to the times, but still pay attention to the essence and basic foundation that must be owned by students, who adhere to the values of Islamic education. The results of this study explain that the reconstruction of Islamic education materials in the era of disruption is 1) having a strong and high awareness and belief in faith; 2) having global insight that still adheres to the values of Islamic education; 3) having foresight; 4) mastering science and technology and achieving; and 5) implementing morals in accordance with the guidance of the Prophet Saw.